Araucaria angustifolia seeds drying behaviour, flour and starch properties (Research, Society and Development, 2020)
A. angustifolia seeds processing allows to extend its offer period. This research had the aim to study differences between fresh and frozen raw seeds drying characteristics, establish the flour microbiological, the starch granule morphologic and pasting properties. The methodology used was laboratory research. The starch was extracted and determined the amylose content, the granules were examined by SEM, the pasting properties by RVA and the thermal behaviour by DSC. The frozen seeds presented higher drying rate, however from the critical moisture, they had similar intern resistance. The starch yield was 19.5% and its amylose content was 12.9%. Through SEM was identified smooth granules without erosion, thus oval and rounded shape. The viscosity pattern corresponds to a matrix with tendency to retrogradation. The starch initial pasting temperature, endothermic peak temperature, complete gelatinization temperature and enthalpy of gelatinization found were, 53.34, 60.32, 67.25 and 2.58 J/g.